Positive effects of Dog Assisted Therapy in the Pediatric Population - Pawluczuk, Paulina; Kusz, Monika; Maślak, Agnieszka; Alzubedi, Adam; Polski, Paweł (Journal of Education, Health and Sport, 2020)
Dog Assisted Therapy is a prevalent part of therapeutic process in pediatric population. It is a modern and constantly developing intervention. Dog Assisted Therapy is utilized with pervasive development disorders. Most of studies confirmed that Autistic Spectrum Disorder, Down Syndrome or Celebral Palsy may benefit from Dog Assisted Therapy. It is important to emphasise the role od Dog Assisted Therapy in improving children mental and physical development.